PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA PERAWAT (Puskesmas Ardimulyo Singosari Kabupaten Malang) - Adi Mulyo S; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this study was to determine the effect of variables on emotional intelligence and spiritual intelligence on nurse performance. The research method used is quantitative. The population and sample used in this study were Ardimulyo Singosari Kab.Malang Public Health Center Nurses. This sampling technique is all nurses, amounting to 35 so that it is worth taking overall so that this research is also called census research, while the data analysis method used in this study is multiple linear regression analysis.The results of this study provide empirical evidence that the variables of emotional intelligence and spiritual intelligence both simultaneously and partially have a positive and significant effect on nurse performance. Keywords: emotional intelligence, spiritual intelligence, nurse performance